PEMANFAATAN LIMBAH AMPAS KELAPA SAWIT SEBAGAI SUBSTRAT UNTUK SINTESIS ZAT GIZI MELALUI FERMENTASI KAPANG RHIZOPUS OLIGOSPORUS (USES OF THE WASTE OF PALM RESIDUE AS SUBSTRATE FOR SYNTHESIZING SOME NUTRIENTS THROUGH RHIZOPUS OLIGOSPORUS FERMENTATION) - Erwin Affandi; Heru Yuniati (Persagi, 2011)
ABSTRACT Background: The residue of palm seeds is the by-products of palm oil. This waste still contains palm oil which can be used as sources of carbon for fermentation in producing the useful substances. Objective: Use of the palm oil residue as the substrate fermentation for the mould of Rhizopus oligosporus. Methods: The residue of palm seeds were treated by adding urea, sucrose and fish oil for the growth of mould. The mould of R.oligosporus was used as mix culture which is used in the fermented soybean. The fermentation was carried out for 3 days in the incubator at 37o C. Product of fermentation were analyzed for the content of water, ash, protein, fat, and fibres. Results: The results indicated the water content of all substrate were changed. The substrate without added nutrient as the control and substrate added urea decreased 29.06 and 11.35 percent, substrate addition of sucrose and fish oil were increasing respectively 26.38 and 19.81 percent. The ash content were increasing for the all substrates, were 79.43; 85.02; 32.97 and 6.06 percent respectively for substrate without addition , substrate with added fish oil, sucrose, urea. The protein contents increased 85.34 and 71.58 percent for substrate without addition, and substrate added fish oil. The highest fat content was in the substrate added sucrose, and 313.09 percent decreasing for the substrate added fish oil. Conclusion: The residue of palm seeds could be used as the substrate fermentation of Rhizopus oligosporus to increase the content of fat after addition of sucrose as the growth supplementation. Keywords: Residue of palm seeds, Rhizopus oligosporus, fermentation. Abstrak Latar belakang: Ampas sawit merupakan produk samping minyak sawit. Limbah masih mengandung minyak, dapat dimanfaatkan sebagai sumber karbon (C) untuk fermentasi dalam menghasilkan senyawa yang bermanfaat. Tujuan: memanfaatkan limbah ampas kelapa sawit sebagai substrat fermentasi kapang Rhizopus oligosporus. Metode: Limbah ampas kelapa sawit sebagai substrat fermentasi ditambah suplemen zat-gizi, yaitu: urea, sukrosa dan minyak ikan untuk pertumbuhan kapang, selain ampas tanpa penambahan sebagai kontrol. Kapang R. oligosporus yang digunakan adalah bentuk laru untuk tempe kedelai. Fermentasi 3 hari pada inkubator suhu 37oC. Produk fermentasi dianalisis kandungan air, abu, protein, lemak dan karbohidrat. Hasil: Hasil analisis menunjukkan bahwa kadar air substrat sebelum dan sesudah fermentasi mengalami perubahan. Substrat ampas sawit sebagai kontrol dan ampas-urea menurun 29,06 dan 11,35 persen, substrat ampas-sukrosa dan ampas-minyak ikan meningkat 26,38 dan 19,81 persen. Kadar abu meningkat pada semua substrat, dan peningkatan tertinggi terjadi pada substrat ampas-minyak ikan dan ampas kontrol 85,02 dan 79,43 persen, kemudian ampas-sukrosa dan ampas-urea 32,97; dan 6,06 persen. Kandungan protein semua substrat meningkat, ampas kontrol dan ampas-minyak ikan cukup tinggi masing-masing sebesar 85,34 dan 71,58 persen. Kandungan lemak tertinggi adalah substrat ampas-sukrosa, sedangkan ampas-minyak ikan malah mengalami penurunan secara drastis sebesar 313,09 persen. Kesimpulan: Limbah ampas kelapa sawit dapat digunakan sebagai substrat fermentasi kapang Rhizopus oligosporus untuk menghasilkan lemak dengan penambahan sukrosa sebagai suplemen pertumbuhan kapang. [Penel Gizi Makan 2011, 34(2): 123-130] Kata kunci: Ampas kelapa sawit, Rhizopus oligosporus, fermentasi